1998
DOI: 10.1002/(sici)1096-9861(19981207)402:1<129::aid-cne9>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependence and cell-type specificity of synergistic neurotrophin actions on spiral ganglion neurons

Abstract: The neurotrophins brain-derived neurotrophin (BDNF) and neurotrophin-3 (NT-3) synergistically enhance survival of spiral ganglion neurons such that simultaneous exposure to both compounds produces a larger response than would be expected from their individual effects. To elucidate the functional role of this neurotrophin interaction, we examined its temporal and cell-type specificity in vitro for both mouse and gerbil spiral ganglion neurons. Synergistic effects were transient; they were maximal within the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 71 publications
7
24
0
Order By: Relevance
“…Peripherin antibody was used to distinguish type II neurons from the total population of spiral ganglion neurons. On the basis of results reported in vivo (Hafidi, 1998) and confirmed in vitro (Mou et al, 1998), this intermediate filament has been found to be enriched in type II spiral ganglion neurons. Monoclonal (MAB 1527; Chemicon, Temecula, CA) and polyclonal (AB-1530; Chemicon) peripherin antisera were used in the following dilutions: 1:75 and 1:4000, respectively.…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…Peripherin antibody was used to distinguish type II neurons from the total population of spiral ganglion neurons. On the basis of results reported in vivo (Hafidi, 1998) and confirmed in vitro (Mou et al, 1998), this intermediate filament has been found to be enriched in type II spiral ganglion neurons. Monoclonal (MAB 1527; Chemicon, Temecula, CA) and polyclonal (AB-1530; Chemicon) peripherin antisera were used in the following dilutions: 1:75 and 1:4000, respectively.…”
Section: Methodssupporting
confidence: 90%
“…Type II neurons, however, possess molecular markers that can be used to distinguish them from type I neurons. We have shown previously that antibodies to the neurofilament protein peripherin label type II neurons preferentially in vitro (Mou et al, 1998). We also observed recently that two of the four family members of the membrane-associated guanylate kinases (MAGUKs), synapse-associated protein (SAP) and SAP102, are enriched in the type II spiral ganglion neurons (Hsu et al, 2002).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…However, various factors can limit the use of peripherin as a type II biomarker. Peripherin immunolabeling can vary with species and tonotopic position (Mou et al 1998). Further, peripherin antibodies label type I as well as type II afferents in the perinatal cochlea (Hafidi et al 1993).…”
Section: Synaptic Structures Of Type II Afferentssupporting
confidence: 91%
“…In addition to exerting a powerful effect on survival (Pirvola et al, 1992;Zheng et al, 1995;Mou et al, 1998;Hossain et al, 2002), BDNF and NT-3 have opposing actions on the firing features of spiral ganglion neurons. BDNF is responsible for fast firing characteristics that typify the basal neurons which transmit high frequency sound signals into the brain; NT-3, however, mediates slower and more heterogeneous firing patterns that characterize the apical neurons which convey low frequency sound information (Davis, 2003).…”
Section: Introductionmentioning
confidence: 99%